Analisis Pengendalian Kualitas untuk Mengurangi Ketidakstabilan Nilai Larutan Brine Chiller Viscose Menggunakan Metode Statistical Process Control pada Departement Chiller di PT. XYZ - Kosim, Komara; Ramdhani, Rizky Fajar; Amalia, Akhsani Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. XYZ is one of the largest artificial rayon fiber companies in the world that produces artificial fibers made from cellulose with quality that matches natural fibers. The purpose of this study is to determine the current quality control method for defective products of viscose brine chiller solution at PT. XYZ. The results of the study revealed that quality control at PT. XYZ is not good, seen from the individual moving range control chart at several points outside the upper control limit, namely: 27, 57 and for the lower control limit, namely: 55.